Secondary battery

CN122930998APending Publication Date: 2026-10-16PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610420784.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-04
Filing Date
2026-04-01
Publication Date
2026-10-16

Smart Images

  • Figure CN122930998A_ABST
    Figure CN122930998A_ABST
Patent Text Reader

Abstract

Provided is a secondary battery suitable for reducing the amount of gas generation in a positive electrode while ensuring energy density. The secondary battery X disclosed herein includes a positive electrode 10, a negative electrode, and a nonaqueous electrolyte solution. The positive electrode 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 on the positive electrode current collector 11. The positive electrode active material layer 12 includes a first layer 12A and a second layer 12B, with the first layer 12A positioned between the positive electrode current collector 11 and the second layer 12B. The first layer 12A includes first positive electrode active material particles, and the second layer 12B includes second positive electrode active material particles. The average particle strength of the second positive electrode active material particles is higher than the average particle strength of the first positive electrode active material particles, and is 190 MPa or greater. The average circularity of the second positive electrode active material particles is 0.95 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a secondary battery. Background Technology

[0002] In recent years, rechargeable and rechargeable secondary batteries, such as lithium-ion batteries, have been used as portable power sources for mobile terminals and other devices, as well as power sources for vehicles such as electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs).

[0003] A secondary battery comprises an assembly as an electrode body containing electrodes (positive and negative electrodes) that undertake the battery reactions during charging and discharging. Its positive electrode has, for example, a sheet-like current collector and a layer of positive electrode active material on the current collector. The positive electrode is manufactured, for example, by coating both sides of the current collector with a positive electrode slurry, and then drying and pressing the resulting coating film. The electrode slurry contains particulate positive electrode active material as the main material. By drying, the liquid components are removed from the coating film on the current collector, forming the positive electrode active material layer. Pressing is performed, for example, using a pair of pressing rollers. By pressing between the pressing rollers, the positive electrode active material layer on the current collector is compressed along the thickness direction, achieving a high capacity density of the positive electrode. Such a secondary battery technology is described, for example, in Patent Document 1 below.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2023-167298 Summary of the Invention

[0007] In the pressing process described above during the positive electrode fabrication, a significant load is placed on the positive electrode active material layer on the current collector. As a result, cracks (pressing cracks) may sometimes form in the positive electrode active material particles within this layer. New exposed surfaces (new surfaces) are created at the locations of these pressing cracks in the positive electrode active material particles. During high-temperature storage tests of the secondary battery, for example, gas may be generated due to contact between this surface and the electrolyte. The generation of this gas can cause degradation of the battery, such as its capacity, and is therefore not preferable.

[0008] This disclosure was conceived under these circumstances, with the aim of providing a secondary battery suitable for reducing gas generation in the positive electrode while ensuring energy density.

[0009] The secondary battery disclosed herein comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode comprises a current collector and a layer of positive electrode active material on the current collector. The positive electrode active material layer comprises a first layer and a second layer, with the first layer located between the current collector and the second layer. The first layer contains first positive electrode active material particles. The second layer contains second positive electrode active material particles. The average particle strength of the second positive electrode active material particles is higher than that of the first positive electrode active material particles, and is 190 MPa or higher. The average sphericity of the second positive electrode active material particles is 0.95 or higher. This type of secondary battery is suitable for reducing gas generation in the positive electrode while ensuring energy density. The reasons are as follows.

[0010] In the positive electrode active material layer of the aforementioned secondary battery (which includes a first layer and a second layer sequentially from the current collector side), as described above, the average particle strength of the second positive electrode active material particles in the second layer is higher than the average particle strength of the first positive electrode active material particles in the first layer, and is 190 MPa or more. In the pressing process of the prior art, this helps to suppress pressing cracks in the positive electrode active material particles in the second layer (which is closer to the pressing roller than the first layer), where the load (pressing load) from the pressing roller is more easily concentrated in the second layer compared to the first layer. The suppression of pressing cracks in the positive electrode active material particles (the aforementioned suppression of the formation and increase of new surfaces) helps to reduce the generation of the aforementioned gas.

[0011] Furthermore, as mentioned above, the average sphericity of the second positive electrode active material particles in the second layer is 0.95 or higher. This helps ensure the slippage between the second positive electrode active material particles in the second layer, thus helping to mitigate the pressure load acting on the second positive electrode active material particles. Mitigating the pressure load on the second positive electrode active material particles helps to suppress pressure cracks in the particles, thereby reducing the generation of the aforementioned gases.

[0012] Furthermore, the first layer of the aforementioned positive electrode active material layer contains first positive electrode active material particles, which are more flexible due to their lower average particle strength compared to the second positive electrode active material particles in the second layer. During the pressing process described above, this helps the first layer act as a buffer between the current collector and the second layer, thereby mitigating the pressing load applied to the second layer. Mitigating the pressing load on the second layer helps suppress pressing cracks in the positive electrode active material particles in the second layer, thereby reducing the generation of the aforementioned gas.

[0013] Furthermore, compared to the second positive electrode active material particles, the first positive electrode active material particles, due to their lower average particle strength and greater flexibility, are more susceptible to deformation under pressure loads and exhibit higher filling capacity (easier densification). The positive electrode active material layer, comprising this first layer of positive electrode active material particles, is suitable for ensuring high capacity density in the positive electrode active material layer or the positive electrode, and thus suitable for ensuring high energy density in secondary batteries.

[0014] As described above, the secondary battery constructed in this way is suitable for reducing the amount of gas generated in the positive electrode while ensuring energy density.

[0015] Preferably, the average particle strength of the first positive electrode active material particles is 160 MPa or less. This configuration is preferred in ensuring the aforementioned buffering function of the first layer in the positive electrode active material layer and the aforementioned filling properties of the first positive electrode active material particles.

[0016] Preferably, the second positive electrode active material particle has a surface portion rich in at least one element selected from Group VIB and Group IIIA elements.

[0017] Preferably, the proportion of the elements selected from Group VIB and Group IIIA elements in the second positive electrode active material particles relative to the total amount of Ni, Co, and Mn is 0.8 mol% to 3.0 mol%. The elements selected from Group VIB and Group IIIA elements are preferably tungsten. These configurations are suitable for achieving a high average particle strength in the second positive electrode active material particles.

[0018] Preferably, the proportion of the elements selected from Group VIB and Group IIIA elements in the first positive electrode active material particles relative to the total amount of Ni, Co, and Mn is less than 0.8 mol%. Such a configuration is preferred in ensuring the buffering function of the first layer in the positive electrode active material layer and the filling properties of the first positive electrode active material particles.

[0019] Preferably, the thickness of the second layer is 5% to 65% of the total thickness of the positive electrode active material layer. This configuration is preferred in that it strikes a good balance between ensuring energy density in the positive electrode and reducing gas production.

[0020] Preferably, the average particle size D of the first positive electrode active material particles is... 50 The particle size is 5 μm to 18 μm. This configuration is preferred in ensuring the buffering function of the first layer in the positive electrode active material layer and the filling properties of the first positive electrode active material particles.

[0021] Preferably, the average particle size D of the second positive electrode active material particles is... 50The particle size is 3μm to 15μm. This configuration is preferred in terms of ensuring the filling of the second positive electrode active material particles in the second layer.

[0022] Preferably, the positive electrode active material constituting the first positive electrode active material particle and / or the second positive electrode active material particle is a positive electrode active material having the compositional formula Li(Li) a Ni x Co y Mn z M α The lithium composite oxide with the following composition is represented by O2 [where -0.1≤a≤0.1, 0.7≤x≤1, 0≤y≤0.3, 0≤z≤0.3, x+y+z=1, 0≤α≤0.1, and M is at least one element selected from B, Al, Mg, Ca, Ti, V, Cr, Ga, Zr, Nb, Mo, In, Hf, Ta, W, Tl]. Such a lithium composite oxide is suitable as a positive electrode active material in secondary batteries to achieve high energy density. Attached Figure Description

[0023] Figure 1 This is a schematic cross-sectional view showing the internal structure of a secondary battery as one embodiment of the present invention.

[0024] Figure 2 It means Figure 1 The diagram shows the configuration of the electrodes in a secondary battery.

[0025] Figure 3 yes Figure 2 A partial, omitted cross-sectional schematic diagram of the positive electrode of the electrode body shown. Detailed Implementation

[0026] The following description, referring to the accompanying drawings, describes a lithium-ion secondary battery as one embodiment of the present invention. It should be noted that in this specification, content other than those specifically mentioned and necessary for the implementation of the present invention (e.g., not representing the general structure and manufacturing process of the secondary battery of the present invention) can be understood as designations made by those skilled in the art based on existing technology. The present invention can be implemented based on the disclosures in this specification and common technical knowledge in the art. Furthermore, in the following drawings, components and parts that perform the same function are labeled with the same symbols. Also, the dimensional relationships (length, width, thickness, etc.) in the drawings do not reflect actual dimensional relationships. It should be noted that in this specification, "secondary battery" generally refers to an energy storage device that can be repeatedly charged and discharged, and is a term that includes energy storage elements such as batteries and double-layer capacitors.

[0027] Figure 1This is a schematic cross-sectional view showing the internal structure of a secondary battery 100 according to one embodiment of the present invention. The secondary battery 100 includes a battery casing 110, an electrode body 120, a positive terminal 130, a negative terminal 140, and a non-aqueous electrolyte (not shown). In this embodiment, the secondary battery 100 is a lithium-ion secondary battery.

[0028] The battery casing 110 serves as the frame of the secondary battery 100, housing the electrode body 120 and non-aqueous electrolyte. In this embodiment, the battery casing 110 has a flat, rectangular (e.g., square) shape. Examples of materials used to construct the battery casing 110 include aluminum, aluminum alloys, iron, and iron alloys. From the viewpoint of balancing lightweight design and required rigidity, aluminum or an aluminum alloy is preferred as the material for the battery casing 110.

[0029] In this embodiment, the battery casing 110 includes a safety valve 111. In this embodiment, the safety valve 111 is located within the battery casing 110... Figure 1 On the upper surface of the battery housing 110, between the positive terminal 130 and the negative terminal 140, a safety valve 111 is a thin-walled portion configured to break when the gas pressure inside the battery housing 110 rises above a predetermined value. This breakage of the safety valve 111 allows gas inside the battery housing 110 to be released outside, preventing or suppressing further pressure increases within the battery housing 110. Additionally, the battery housing 110 has an injection port (not shown) for injecting a non-aqueous electrolyte into the battery housing 110. After the non-aqueous electrolyte is injected, the injection port is sealed by a sealing member.

[0030] Figure 2 This is a schematic diagram showing the structure of the electrode body 120. The electrode body 120 includes a stacked structure in which a positive electrode 10 and a negative electrode 20 are alternately arranged by an insulating member 30. In this embodiment, the electrode body 120 is a flat wound electrode body, and is formed by winding a strip-shaped stacked body (having a width in a direction orthogonal to its long side direction) consisting of a strip-shaped positive electrode 10, a strip-shaped insulating member 30, a strip-shaped negative electrode 20, and another strip-shaped insulating member 30 arranged in sequence. Instead of this configuration, the electrode body 120 may also be a stacked electrode body in which a square positive electrode and a square negative electrode are stacked in a mutually insulated state.

[0031] The positive electrode 10 has a positive current collector 11 and a positive active material layer 12. In this embodiment, the positive electrode 10 has a positive active material layer 12 on both sides of the positive current collector 11 (see details). Figure 3 (To be described later). Figure 2 As shown, one end of the positive current collector 11 in the width direction W of the electrode body 120 or the positive electrode 10 ( Figure 2The left end has a portion 11a. The width direction W refers to the direction orthogonal to the long side direction of the strip-shaped laminate described above. The portion 11a is the exposed area in the positive electrode current collector 11 where the positive electrode active material layer 12 is not laminated. In the electrode body 120 with the wound electrode body, the portion 11a overlaps in the lamination direction of the laminated structure of the electrode body 120, and functions as a current collector. The portion 11a is connected to the positive electrode current collector plate 131 after being overlapped into one piece. Examples of materials for the positive electrode current collector plate 131 include aluminum and aluminum alloys. Examples of methods for connecting the positive electrode current collector plate 131 to the portion 11a in the positive electrode 10 include ultrasonic bonding and laser welding.

[0032] The negative electrode 20 has a negative current collector 21 and a negative active material layer 22. In this embodiment, the negative electrode 20 has a negative active material layer 22 on both sides of the negative current collector 21 (not shown). The negative current collector 21 is preferably a strip-shaped conductive metal foil. Examples of materials for the negative current collector 21 include copper, copper alloys, nickel, and stainless steel, with copper foil being preferred. The negative active material layer 22 contains a negative active material capable of reversibly absorbing and releasing charge carriers. Examples of negative active materials include carbon materials such as graphite, hard carbon, and soft carbon. Graphite can be natural graphite or artificial graphite. The negative active material can also be a silicon-containing material. Examples of silicon-containing materials include silicon (Si), silicon oxide represented by SiOx (0.05 < x < 1.95), Si-C composites containing Si particles in carbon particles, and lithium silicate (LixSiyOz). The negative active material layer 22 may contain additives other than the negative active material. Examples of additives include adhesives and thickeners. Examples of adhesives include rubbers such as styrene-butadiene rubber (SBR) and fluorinated resins such as polyvinylidene fluoride (PVDF). Examples of thickeners include cellulose-based resins such as carboxymethyl cellulose (CMC).

[0033] The negative current collector 21 has a portion 21a at the other end (right end in the figure) in the width direction W of the electrode body 120 or the negative electrode 20. The portion 21a is the exposed area in the negative current collector 21 where the negative electrode active material layer 22 is not formed. In the electrode body 120 wound around the electrode body, the portion 21a overlaps in the stacking direction of the aforementioned stacked structure of the electrode body 120, functioning as a current collector. The portion 21a is connected to the negative current collector plate 141 in this overlapping and integrated state. Examples of materials used to construct the negative current collector plate 141 include copper and copper alloys. Examples of methods for connecting the negative current collector plate 141 to the portion 21a in the negative electrode 20 include ultrasonic bonding and laser welding.

[0034] The separator 30 is a component used to insulate the positive electrode active material layer 12 from the negative electrode active material layer 22 and to maintain the ionic conductivity of the electrolyte between the two layers. The separator 30 is preferably a porous resin sheet made of polyolefin resin. Examples of polyolefin resins include polyethylene (PE) and polypropylene (PP). A heat resistance layer (HRL) containing inorganic fillers may also be provided on the surface of the separator 30. Examples of materials constituting the inorganic fillers include alumina, boehmite, aluminum hydroxide, and titanium dioxide.

[0035] like Figure 1 As shown, the positive terminal 130 is mounted on the battery casing 110. For example, the battery casing 110 has a terminal opening that extends through its constituent parts (plates) in the thickness direction, and the positive terminal 130 is mounted on this opening with an insulating washer sandwiched between it and the battery casing 110. Riveting is one possible method for mounting the positive terminal 130. Furthermore, the positive terminal 130 is exposed both outside and inside the battery casing 110. Inside the battery casing 110, the positive terminal 130 is connected to the positive current collector 131. The positive terminal 130 is electrically connected to the positive electrode 10 of the electrode body 120 via the positive current collector 131. This positive terminal 130 is preferably made of metal, more preferably of aluminum or an aluminum alloy.

[0036] The negative terminal 140 is also mounted on the battery housing 110 (the mounting method is the same as described above for the positive terminal 130). The negative terminal 140 is exposed both outside and inside the battery housing 110. Inside the battery housing 110, the negative terminal 140 is connected to the negative current collector 141. The negative terminal 140 is electrically connected to the negative terminal 20 of the electrode body 120 via the negative current collector 141. Such a negative terminal 140 is preferably made of metal, more preferably of copper or a copper alloy.

[0037] The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte (supporting salt). Examples of non-aqueous solvents include ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC). The non-aqueous solvent can be used alone or in combination with two or more. The electrolyte is a lithium salt, preferably a fluorinated lithium salt. Examples of fluorinated lithium salts include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium bis(fluorosulfonyl)imide (LiN(SO2F)2). The electrolyte can be used alone or in combination with two or more. This non-aqueous electrolyte is contained within the electrode body 120 within the battery casing 110. Any remaining non-aqueous electrolyte not contained within the electrode body 120 can also be stored inside the battery casing 110.

[0038] Figure 3 This is a partially omitted cross-sectional view of the elongated sheet-shaped positive electrode 10 in the width direction W. The positive electrode 10 has a positive current collector 11 and positive active material layers 12 disposed on both sides of the positive current collector 11 in the thickness direction D. Each positive active material layer 12 includes a first layer 12A and a second layer 12B. In each positive active material layer 12, the first layer 12A is located between the positive current collector 11 and the second layer 12B. In this embodiment, the first layer 12A is located on the positive current collector 11, and the second layer 12B is located on the first layer 12A, with the second layer 12B being the outermost layer of the positive active material layer 12. In other embodiments, the positive active material layer 12 may also include other layers. These other layers may, for example, be located between the positive current collector 11 and the first layer 12A.

[0039] Examples of positive electrode current collectors 11 include conductive metal foil and resin sheets with conductive metal layers on both sides. Examples of conductive metals used for the positive electrode current collector 11 include aluminum, aluminum alloys, nickel, titanium, and stainless steel, with aluminum being preferred. From the viewpoint of ensuring the strength of the positive electrode current collector 11 and consequently the strength of the positive electrode 10, the thickness of the positive electrode current collector 11 is preferably 5 μm or more, more preferably 8 μm or more. From the viewpoint of suppressing the volume occupied by the positive electrode current collector 11 to ensure the volumetric energy density of the secondary battery 100, the thickness of the positive electrode current collector 11 is preferably 30 μm or less, more preferably 20 μm or less.

[0040] The first layer 12A of the positive electrode active material layer 12 contains the first positive electrode active material particles (the first CAM particles). The first CAM particles are, for example, particles containing a composite oxide (lithium composite oxide) containing lithium (Li) and other metal elements.

[0041] The lithium composite oxide is preferably a nickel (Ni)-containing lithium composite oxide, more preferably a high-Ni-content lithium composite oxide with a Ni content of 70 mol% (relative to the proportion of metal elements other than Li) or more. This configuration is preferred in terms of achieving high energy density in the secondary battery 100 at low cost. Examples of Ni-containing lithium composite oxides constituting the first CAM particle include lithium-nickel composite oxides, lithium-nickel-cobalt composite oxides, lithium-nickel-manganese composite oxides, lithium-nickel-cobalt-manganese composite oxides, lithium-nickel-cobalt-aluminum composite oxides, and lithium-iron-nickel-manganese composite oxides. These can be used individually or in combination of two or more. From the viewpoint of simultaneously ensuring long cycle life, good thermal stability, and high energy density in the secondary battery 100, lithium-nickel-cobalt-manganese composite oxides are preferred as Ni-containing lithium composite oxides.

[0042] The positive electrode active material constituting the first CAM particle (the first positive electrode active material) preferably has the composition represented by the following composition formula (1).

[0043] Li (Li) a Ni x Co y Mn z M α O2 (1)

[0044] [In the formula, -0.1≤a≤0.1, 0.7≤x≤1, 0≤y≤0.3, 0≤z≤0.3, x+y+z=1, 0≤α≤0.1, and M is at least one element selected from B, Al, Mg, Ca, Ti, V, Cr, Ga, Zr, Nb, Mo, In, Hf, Ta, W, and Tl.]

[0045] In composition formula (1), a satisfies -0.1≤a≤0.1, preferably 0≤a≤0.1. From the viewpoint of achieving high energy density in the secondary battery 100 at low cost, x satisfies 0.7≤x≤1, preferably 0.75≤x≤1, and more preferably 0.8≤x≤1. From the viewpoint of improving the structural stability of the positive electrode active material and reducing resistance, y satisfies 0≤y≤0.3, preferably 0.1≤y≤0.3. From the viewpoint of improving the structural stability of the positive electrode active material and reducing cost, z satisfies 0≤z≤0.3, preferably 0.1≤z≤0.3. The composition of the positive electrode active material (the first positive electrode active material and the second positive electrode active material described later) can be confirmed, for example, by high-frequency inductively coupled plasma (ICP) emission spectroscopy analysis.

[0046] Examples of crystal structures for Ni-lithium composite oxides include layered rock salt and spinel-type crystal structures, with layered rock salt crystal structures being preferred. The crystal structure can be confirmed, for example, by X-ray crystal structure diffraction.

[0047] The shape of the first CAM particle can be, for example, approximately spherical, ellipsoidal, or sheet-like, with approximately spherical being preferred. In this specification, "approximately spherical" means a shape that can be considered as a large sphere as a whole, and refers to a shape with an average aspect ratio (length / width ratio) of approximately 1 to 2, for example, in the range of 1 to 1.5, based on cross-sectional observation images from an electron microscope.

[0048] From the viewpoint of ensuring the filling of the first CAM particles in the first layer 12A, the average roundness of the first CAM particles is preferably 0.90 or higher, more preferably 0.91 or higher, and even more preferably 0.92 or higher. From the viewpoint of reducing the manufacturing cost of the secondary battery 100, the average roundness of the first CAM particles is preferably 1.00 or lower, more preferably 0.99 or lower, and even more preferably 0.98 or lower. As a method for adjusting the average roundness of the CAM particles (the first CAM particles and the second CAM particles described later), mechanical post-processing can be cited as an example. As a mechanical post-processing, it is preferable to use a method such as a ball mill to remove the edges and corners of the particles. In such a process, the average roundness can be improved by extending the processing time. The method for measuring the average roundness of the CAM particles is described later in the context of experimental examples.

[0049] From the perspective of ensuring particle strength, the average particle size D of the 1CAM particle is... 50 Preferably, the particle size is 5 μm or more, more preferably 7 μm or more, and even more preferably 9 μm or more. From the viewpoint of ensuring the filling of the first CAM particles in the first layer 12A, the average particle size D of the first CAM particles is... 50 Preferably, the particle size is 18 μm or less, more preferably 15 μm or less, and even more preferably 12 μm or less. The average particle size D of the CAM particles (first CAM particles, second CAM particles described later) 50 It is the median particle size in the volumetric particle size distribution (the particle size at which the volumetric cumulative frequency reaches 50% from the small diameter side), which can be determined, for example, from the particle size distribution obtained using laser diffraction and scattering methods. The average particle size D of CAM particles is... 50 Methods for adjusting these conditions include, for example, adjusting the conditions during the reaction based on the crystallization method described later, which is used to obtain a complex hydroxide as a precursor for the positive electrode active material. Examples of such conditions include, for example, various concentrations in the reaction solution such as temperature, pH, stirring speed, and ammonium ion concentration, as well as the reaction time.

[0050] The first CAM particle can be a primary particle or a secondary particle formed by the condensation of multiple primary particles through physical or chemical bonding forces. Preferably, it is a secondary particle with gaps between the condensed primary particles inside.

[0051] The average particle strength of the first CAM particles is preferably 110 MPa or more, more preferably 125 MPa or more, and even more preferably 140 MPa or more. This configuration is preferred in suppressing compression cracks in the first CAM particles in the first layer 12A during the pressing process described later in the manufacturing process of the secondary battery 100. The average particle strength of the first CAM particles is preferably 160 MPa or less, more preferably 155 MPa or less, and even more preferably 150 MPa or less. This configuration is preferred in ensuring the softness of the first CAM particles in the first layer 12A to achieve high filling density during the pressing process described later in the manufacturing process of the secondary battery 100. The average particle strength of the first CAM particles can be obtained as the average value of the crush strength of the first CAM particles. The crush strength of particles such as the first CAM particles can be measured, for example, using an ultra-micro indentation hardness tester (product name "ENT-5", manufactured by Elionix). The method for deriving the average particle strength of CAM particles (first CAM particles, second CAM particles described later) is as described later in the test examples. As a method for adjusting the average particle strength of CAM particles, one example is adjusting the conditions during the reaction based on the crystallization method described later, which is used to obtain a composite hydroxide as a precursor of the positive electrode active material. Examples of such conditions include various concentrations of the reaction solution such as temperature, pH, stirring speed, and ammonium ion concentration, as well as the reaction time. Another method for adjusting the average particle strength of CAM particles is adjusting the firing temperature of the CAM particles and selecting the type and amount of coating elements to be added (described later).

[0052] The first CAM particle and the second CAM particle (described later) may also have a surface layer rich in at least one element selected from Group VIB and Group IIIA elements. The enriched surface layer refers to a region extending 20% ​​from the outermost surface of the particle to the particle center, where the concentration of the aforementioned element (coating element) is higher than that at the particle center. The particle center may or may not contain the aforementioned element (coating element). Examples of Group VIB elements include Cr, Mo, and W; examples of Group IIIA elements include B, Al, Ga, In, and Tl. The proportion of the aforementioned coating element relative to the total amount of Ni, Co, and Mn (Ni + Co + Mn) in the first CAM particle is preferably less than 0.8 mol%, preferably less than 0.7 mol%, and more preferably less than 0.6 mol%. In CAM particles (the first CAM particle and the second CAM particle (described later), the higher the proportion of the coating element relative to the total amount of the aforementioned metal elements (Ni + Co + Mn), the higher the concentration of the coating element in the surface layer tends to be. Furthermore, for CAM particles (the first CAM particle and the second CAM particle described later) containing the aforementioned coating elements, the presence of the coating elements in the surface layer can be confirmed, for example, by LA-ICP-MS (Laser Ablation Inductively Coupled Plasma Mass Spectrometry) analysis.

[0053] Layer 12A may also contain additives other than the 1CAM particles. Examples of additives include other positive electrode active material particles, conductive agents, binders, and lithium triphosphate. Examples of conductive agents include acetylene black, Ketjen black, graphite, and carbon nanotubes. Examples of binders include fluorinated resins such as polyvinylidene fluoride (PVDF) and rubbers such as styrene-butadiene rubber (SBR).

[0054] The second layer 12B of the positive electrode active material layer 12 contains second positive electrode active material particles (second CAM particles). The second CAM particles are, for example, lithium composite oxide particles. The lithium composite oxide constituting the second CAM particles is preferably a Ni-containing lithium composite oxide, more preferably a high-Ni-content lithium composite oxide with a Ni content of 70 mol% (relative to the proportion of metal elements other than Li) or more. Such a configuration is preferred in terms of achieving high energy density in the secondary battery 100 at low cost. Examples of the Ni-containing lithium composite oxide constituting the second CAM particles include, for example, the aforementioned Ni-containing lithium composite oxide with respect to the first CAM particles, preferably a lithium-nickel-cobalt-manganese composite oxide.

[0055] The positive electrode active material constituting the second CAM particle (the second positive electrode active material) preferably has the composition represented by the above-described compositional formula (1). The preferred proportions of the elements in compositional formula (1) are the same for the second CAM particle as those for the first CAM particle. Furthermore, the crystal structure, particle shape, and particle aggregation morphology (primary particles, secondary particles) of the second positive electrode active material constituting the second CAM particle are the same as those of the first positive electrode active material constituting the first CAM particle.

[0056] The average sphericity of the second CAM particles is 0.95 or higher, preferably 0.96 or higher, and more preferably 0.97 or higher. These properties help ensure the slippage between the second CAM particles in the second layer 12B during the pressing process described later in the manufacturing process of the secondary battery 100, thus helping to mitigate the pressing load acting on the second CAM particles. The average sphericity of the second CAM particles is 1.0 or lower, and from the viewpoint of reducing the manufacturing cost of the secondary battery 100, it is preferably 0.99 or lower, and more preferably 0.98 or lower.

[0057] From the perspective of ensuring particle strength, the average particle size D of the 2CAM particle is... 50 Preferably, the particle size is 3 μm or more, more preferably 4 μm or more, and even more preferably 5 μm or more. From the viewpoint of ensuring the filling of the second CAM particles in the second layer, the average particle size D of the second CAM particles is... 50 Preferably, it is 15 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less.

[0058] The average particle strength of the second CAM particles is higher than that of the first CAM particles. The average particle strength of the second CAM particles is preferably 190 MPa or more, more preferably 200 MPa or more, and even more preferably 210 MPa or more. These features, in the pressing process described later in the manufacturing process of the secondary battery 100, help suppress pressing cracks in the positive electrode active material particles in the second layer 12B (which is closer to the pressing roller than the first layer 12A), wherein the pressing load is more easily concentrated in the second layer 12B compared to the first layer 12A. The average particle strength of the second CAM particles is, for example, 300 MPa or less, 280 MPa or less, or 250 MPa or less.

[0059] The second CAM particle has a surface layer rich in at least one element (coating element) selected from Group VIB and Group IIIA elements. The coating element concentration in the surface layer of the second CAM particle is higher than that in the surface layer of the first CAM particle. The coating element is more preferably at least one element selected from W, Mo, Cr, B, Al, Ga, In, and Tl, and even more preferably W. The ratio of the coating element to the total amount of Ni, Co, and Mn in the second CAM particle (Ni + Co + Mn) is preferably 0.8 mol% or more, preferably 1.5 mol% or more, even more preferably 1.9 mol% or more, and particularly preferably 2.2 mol% or more. The above configuration of the surface layer of the second CAM particle is suitable for achieving a high average particle strength in the second CAM particle. From the viewpoint of ensuring the energy density of the secondary battery 100, the ratio of the coating element to the total amount of the metal elements (Ni + Co + Mn) in the second CAM particle is preferably 3.0 mol% or less, preferably 2.7 mol% or less, and even more preferably 2.5 mol% or less.

[0060] The second layer 12B may also contain additives other than the second CAM particles. As additives, examples include other positive electrode active material particles, conductive agents, binders, and lithium triphosphate, similar to those mentioned above regarding the first CAM particles.

[0061] In this embodiment, the total thickness of the positive electrode active material layer 12 is the sum of the thickness of the first layer 12A and the thickness of the second layer 12B. From the viewpoint of ensuring minimum operability as an electrode plate, the total thickness of the positive electrode active material layer 12 is preferably 30 μm or more, more preferably 40 μm or more. From the viewpoint of ensuring good rate performance in the secondary battery 100, the total thickness of the positive electrode active material layer 12 is preferably 100 μm or less, more preferably 90 μm or less, and even more preferably 80 μm or less. Furthermore, the thickness of the first layer 12A is, for example, 15 μm or more, preferably 20 μm or more, for example, 90 μm or less, and preferably 80 μm or less. The thickness of the second layer 12B is, for example, 3 μm or more, preferably 5 μm or more, for example, 50 μm or less, and preferably 40 μm or less.

[0062] From the viewpoint of suppressing particle cracks in the second layer 12B, which experiences stress concentration during the pressing of the positive electrode 10, the thickness of the second layer 12B relative to the total thickness of the positive electrode active material layer 12 is preferably 5% or more, more preferably 8% or more, and even more preferably 10% or more. From the viewpoint of ensuring the energy density in the positive electrode 10, the thickness of the second layer 12B relative to the total thickness of the positive electrode active material layer 12 is preferably 65% ​​or less, more preferably 45% or less, and even more preferably 25% or less.

[0063] The aforementioned positive electrode active material particles (first and second CAM particles) can be manufactured, for example, as follows.

[0064] First, a composite hydroxide, serving as a precursor for the positive electrode active material (lithium composite oxide), is obtained via crystallization. In the crystallization process, for example, an aqueous solution containing a specified metal salt is added dropwise to a pH-adjusted reaction solution while stirring (crystallization reaction). The reaction solution is, for example, ion-exchanged water with a pH of 7. The aqueous solution contains, at a specified concentration, the metal salts of each metal element (excluding lithium and the coating element mentioned above) used as a supply source for the positive electrode active material to be produced. Depending on the composition of the positive electrode active material to be produced, for example, nickel salts, cobalt salts, and manganese salts can be used. For example, nickel sulfate, nickel nitrate, or nickel carbonate can be used as nickel salts. For example, cobalt sulfate, cobalt nitrate, or cobalt carbonate can be used as cobalt salts. For example, manganese sulfate, manganese nitrate, or manganese carbonate can be used as manganese salts. Regarding the reaction solution in the crystallization reaction, the temperature is maintained at, for example, 25°C, the pH is maintained at, for example, 10–13 by adding an alkaline aqueous solution (e.g., sodium hydroxide aqueous solution), and the ammonium ion concentration is controlled at 10–15 g / L by adding an alkaline aqueous solution containing ammonium ions (e.g., ammonia). This crystallization reaction causes the composite hydroxide, a precursor of the positive electrode active material, to precipitate (co-precipitate). The resulting co-precipitate (hydroxide particles) is then filtered, washed with water, and dried. This yields a powder of the composite hydroxide, a precursor of the positive electrode active material.

[0065] Next, the obtained composite hydroxide powder is dry-mixed with lithium hydroxide (LiOH) powder at a specified ratio to prepare a mixed powder (preparation of the first mixed powder). Then, the mixed powder is calcined, for example, in an atmospheric atmosphere. The calcination temperature is set to, for example, 650°C to 900°C, and the calcination time is set to, for example, 9 to 15 hours. Thus, a lithium composite oxide powder with a specified composition is obtained.

[0066] After adding the aforementioned coating elements to the positive electrode active material particles, the resulting lithium composite oxide powder and the oxide powder of the coating element are then dry-mixed at a predetermined ratio to prepare a mixed powder (preparation of the second mixed powder). The oxide of the coating element, depending on the type of coating element to be added, can be, for example, tungsten oxide (e.g., WO3), boric acid, and aluminum oxide. Next, the mixed powder is calcined, for example, in an atmospheric atmosphere. The calcination temperature is set to, for example, 300°C, and the calcination time is set to, for example, 1 to 3 hours. Thus, positive electrode active material particles with a surface rich in the aforementioned coating elements can be obtained.

[0067] With the sphericity of the positive electrode active material particles adjusted, the obtained positive electrode active material particles are subjected to ball milling treatment using a ball milling device. In the ball milling treatment, the rotation speed is set to, for example, 100 to 200 rpm, the treatment time is set to, for example, 1 to 2 hours, and the ball diameter (Φ) is set to, for example, 2 to 5 mm.

[0068] The first positive electrode active material particles used to form the first layer 12A of the positive electrode 10 and the second positive electrode active material particles used to form the second layer 12B can be manufactured, for example, by the method described above. Furthermore, in the fabrication of the positive electrode 10 of the secondary battery 100, a first positive electrode slurry containing the first positive electrode active material particles and a second positive electrode slurry containing the second positive electrode active material particles are prepared respectively. Examples of solvents used for slurry preparation include N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), and isopropanol. The first and second positive electrode slurries each contain, as needed, the aforementioned additives (conductive agents and binders, etc.) other than the positive electrode active material particles. Next, by coating and drying the first positive electrode slurry and the second positive electrode slurry on one surface of the positive electrode current collector 11, a positive electrode active material layer is formed. Next, a positive electrode active material layer is formed by coating and drying a first positive electrode slurry and a second positive electrode slurry on the other side of the positive electrode current collector 11. Then, for example, by pressing between a pair of pressing rollers, the positive electrode active material layers on both sides of the positive electrode current collector 11 are compressed in the thickness direction, forming a compacted (high capacity density) positive electrode active material layer 12 on both sides of the positive electrode current collector 11 (pressing process). By performing the above, a positive electrode 10 can be manufactured. The aforementioned secondary battery 100 can be manufactured with an electrode body 120, which includes this positive electrode 10 as the positive electrode that undertakes the battery reaction during charging and discharging.

[0069] The secondary battery 100 is suitable for reducing the amount of gas generated in the positive electrode 10 while ensuring energy density. The reasons are as follows.

[0070] In the positive electrode active material layer 12 of the secondary battery 100 (which sequentially includes a first layer 12A and a second layer 12B from the positive electrode current collector 11 side), as described above, the average particle intensity of the second CAM particles in the second layer 12B is higher than the average particle intensity of the first CAM particles in the first layer 12A. This helps to suppress pressing cracks in the second CAM particles in the second layer 12B (which is closer to the pressing roller than the first layer 12A) during the pressing process in the manufacturing process of the secondary battery 100, where the load (pressing load) from the pressing roller is more easily concentrated in the second layer 12B compared to the first layer 12A. Suppressing pressing cracks in the second CAM particles also suppresses the formation of new exposed surfaces (newly formed surfaces) on the second CAM particles, and suppresses gas generation caused by contact between the newly formed surfaces and non-aqueous electrolytes.

[0071] Furthermore, as mentioned above, the average roundness of the 2CAM particles in the second layer 12B is 0.95 or higher. This helps ensure the slippage between the 2CAM particles in the second layer 12B, thus helping to mitigate the compressive load acting on the 2CAM particles. Mitigating the compressive load on the 2CAM particles helps to suppress compressive cracks in the particles, thereby reducing the generation of the aforementioned gases.

[0072] Furthermore, the first layer 12A of the positive electrode active material layer 12 contains first CAM particles, which are more flexible due to their lower average particle strength compared to the second CAM particles in the second layer 12B. This helps the first layer 12A act as a buffer between the positive electrode current collector 11 and the second layer 12B during the pressing process, thereby mitigating the pressing load applied to the second layer 12B. Mitigating the pressing load on the second layer 12B helps suppress pressing cracks in the second CAM particles within the second layer 12B, thereby reducing the generation of the aforementioned gases.

[0073] Furthermore, compared to the second CAM particles, the first CAM particles, due to their lower average particle strength and greater flexibility, are more susceptible to deformation under pressure loads and have higher filling capacity (easier to densify). The positive electrode active material layer 12 has a first layer 12A containing these first CAM particles, which is suitable for ensuring a high capacity density in the positive electrode active material layer 12 or the positive electrode 10, and therefore suitable for ensuring a high energy density in the secondary battery 100.

[0074] As described above, the secondary battery 100 configured as described above reduces the amount of gas generated in the positive electrode 10 while ensuring energy density.

[0075] In the above embodiment, the secondary battery 100 is described as a square secondary battery having a flat electrode body 120. However, the secondary battery disclosed herein can also be a secondary battery of other shapes and forms. For example, the technology disclosed herein can also be applied to lithium-ion secondary batteries having stacked electrode bodies, cylindrical lithium-ion secondary batteries, laminated lithium-ion secondary batteries, etc.

[0076] [Experimental Example]

[0077] The following describes test examples related to the present invention, but it is not intended to limit the present invention to the contents shown in these test examples.

[0078] [Example 1]

[0079] [The production of the positive electrode]

[0080] The positive electrode in Example 1 was fabricated by the following steps: fabrication of the first positive electrode active material, fabrication of the second positive electrode active material, and formation of the positive electrode active material layer.

[0081] <Preparation of the First Positive Electrode Active Material>

[0082] In the preparation of the first positive electrode active material (1CAM), a nickel-cobalt-manganese (NCM) composite hydroxide, which serves as the precursor of 1CAM, is first obtained. Specifically, a raw material aqueous solution and a reaction solution are prepared first. The reaction solution is prepared in a 5L reaction tank. The raw material aqueous solution contains nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of Ni:Co:Mn = 80:10:10, with a total concentration of 1.5 mol / L for these metal salts. The reaction solution is ion-exchanged water, which has undergone treatment to remove dissolved oxygen by introducing an inactive gas and to adjust the pH (based on a 25°C standard) to 10.5–11.5 by adding an aqueous sodium hydroxide solution (during which time the liquid temperature is maintained at 30°C). Next, while stirring the reaction solution (stirring speed 600 rpm), the raw material aqueous solution is added dropwise to the reaction solution, causing the NCM composite hydroxide to precipitate (co-precipitate) through a crystallization reaction. The reaction solution during dropwise addition was maintained at 25°C–35°C, the pH was maintained at 10.5–11.5 by adding sodium hydroxide aqueous solution, and the ammonium ion concentration was controlled at 10 g / L by adding ammonia water (crystallization was carried out for 20 hours under the above conditions). Next, the obtained co-precipitated product (hydroxide particles) was filtered and washed with water, then dried in an oven at 120°C to obtain powder. Thus, the NCM composite hydroxide (Ni) was obtained as a precursor to the first CAM. 0.8 Co 0.1 Mn 0.1 (OH)2) powder.

[0083] Next, the obtained NCM composite hydroxide powder was mixed with lithium hydroxide (LiOH) powder at a molar ratio of Li:(Ni+Co+Mn) = 1.05:1.00 to prepare a mixed powder (preparation of the first mixed powder). Then, the mixed powder was calcined at 770°C for 15 hours under atmospheric conditions (first calcination treatment). This yielded the lithium composite oxide powder.

[0084] Next, the obtained lithium composite oxide powder was mixed with tungsten oxide (WO3) powder at a composition of (Ni + Co + Mn):W = 1.000:0.005 to prepare a mixed powder (preparation of the second mixed powder). Then, this mixed powder was calcined at 300°C for 3 hours under atmospheric conditions (second calcination treatment). This yielded the first CAM powder. The particles in this powder are tungsten-rich first CAM particles, Li (Li₂O₃). 0.05 Ni0.8 Co 0.1 Mn 0.1 W 0.005 O2, W ratio: 0.5 mol%, average particle size D 50 (10μm).

[0085] <Preparation of the Second Positive Electrode Active Material>

[0086] In the preparation of the second positive electrode active material (2CAM), firstly, a nickel-cobalt-manganese (NCM) composite hydroxide, which serves as the precursor of the 2CAM, is obtained. Specifically, firstly, a raw material aqueous solution and a reaction solution are prepared. The reaction solution is prepared in a 5L reaction tank. The raw material aqueous solution contains nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of Ni:Co:Mn = 80:10:10, with a total concentration of 1.5 mol / L for these metal salts. The reaction solution is ion-exchanged water, which has undergone treatment to remove dissolved oxygen by introducing an inactive gas and to adjust the pH (based on a 25°C standard) to 12.0–12.5 by adding an aqueous sodium hydroxide solution (during which time the liquid temperature is maintained at 30°C). Next, in the first step of crystallization, the raw material aqueous solution is added dropwise to the reaction solution while stirring (stirring speed 500 rpm), causing the NCM composite hydroxide to precipitate (co-precipitate) through a crystallization reaction. For the reaction solution during dropwise addition, the temperature was maintained at 25℃–35℃. The pH was maintained at 12.0–12.5 by adding sodium hydroxide aqueous solution, and the ammonium ion concentration was controlled at 10 g / L by adding ammonia water. The crystallization time was set to 1 hour. Next, in the second step of crystallization, the pH of the reaction solution was adjusted to 10.5–11.5 by dropwise addition of sulfuric acid, and the NCM composite hydroxide was precipitated (co-precipitated) for 20 hours under the same conditions as in the first step. The resulting co-precipitated product (hydroxide particles) was then filtered, washed with water, and dried in an oven at 120℃ to obtain a powder. Thus, the NCM composite hydroxide (Ni) was obtained as a precursor to the second CAM. 0.8 Co 0.1 Mn 0.1 (OH)2) powder.

[0087] Next, the obtained NCM composite hydroxide powder was mixed with lithium hydroxide (LiOH) powder at a molar ratio of Li:(Ni+Co+Mn) = 1.05:1.00 to prepare a mixed powder (preparation of the first mixed powder). This mixed powder was then calcined at 780°C for 4 hours under atmospheric conditions, followed by calcination at 900°C for 5 hours (first calcination treatment). This yielded a lithium composite oxide powder.

[0088] Next, the obtained lithium composite oxide powder and tungsten oxide (WO3) powder were dry-mixed using an automatic mortar with a composition of (Ni + Co + Mn):W = 1.000:0.010 to prepare a mixed powder (preparation of the second mixed powder). Then, this mixed powder was calcined at 300°C for 3 hours under atmospheric conditions (second calcination). This yielded the second CAM powder. The particles in this powder are tungsten-rich second CAM particles, Li (Li₂O₃). 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.010 O2, W ratio: 1.0 mol%, average particle size D 50 (4.0μm).

[0089] Next, ball milling was performed. Specifically, a ball milling apparatus (trade name "Pulnerisette 5 planetary ball mill", manufactured by Fritsch) and zirconia balls (made by NIKKATO, average diameter 2 mm) as the milling media were used to ball mill the second CAM at a speed of 100 rpm and a processing time of 1 hour. During this ball milling process, the volume ratio of balls, sample, and remaining space was adjusted to approximately 1:1:1, and the apparatus was paused every 15 minutes to mix the sample with the balls. This yielded a second CAM powder with improved sphericity. The particles in this powder were second CAM particles with a surface rich in tungsten (Li(Li)2)2. 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.01 O2, W ratio: 1.0 mol%, average particle size D50: 4.0 μm.

[0090] <Formation of the Positive Electrode Active Material Layer>

[0091] First, a positive current collector and a first and a second positive electrode slurry are prepared, along with a first and a second layer for forming a positive active material layer (CAM layer) on the positive current collector. The positive current collector is an aluminum foil with a thickness of 13 μm. The first positive electrode slurry is obtained by kneading a mixture containing the aforementioned first CAM, carbon black (CB) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio of first CAM:CB:PVDF = 100:1.5:1, and further containing a specified amount of N-methyl-2-pyrrolidone (NMP) as a solvent. The second positive electrode slurry is obtained by kneading a mixture containing the aforementioned second CAM, CB, and PVDF in a mass ratio of second CAM:CB:PVDF = 100:1.5:1, and further containing a specified amount of NMP. Next, a CAM layer (layer 1 and layer 2) is formed by coating and drying a first positive electrode slurry and a second positive electrode slurry on one side of the positive current collector. Then, a CAM layer (layer 1 and layer 2) is formed by coating and drying the first positive electrode slurry and the second positive electrode slurry on the other side of the positive current collector. Finally, the positive current collector with the CAM layer is calendered using calendering rollers to achieve a CAM layer thickness of 70 μm and a density of 3.6 g / cm³. 3 (CAM layer rolling process). Thus, a positive electrode with a double-layer CAM layer disposed on both sides of the positive current collector is obtained. The thickness ratio of the second layer in each CAM layer is 10% (first layer: second layer = 9:1 [thickness ratio], the thickness ratio of the second layer to the first layer is 0.11).

[0092] The positive electrode in Example 1 is fabricated as described above. The positive electrode in Example 1 has a CAM layer (layer 2 / layer 1) / positive current collector (aluminum foil) / CAM layer (layer 1 / layer 2) stacked together.

[0093] [Making the negative electrode]

[0094] First, a negative electrode current collector and a negative electrode slurry for forming a negative electrode active material layer (AAM layer) on the negative electrode current collector are prepared. The negative electrode current collector is a copper foil with a thickness of 8 μm. The negative electrode slurry is obtained by mixing graphite as the negative electrode active material (AAM), styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in ion-exchanged water at a mass ratio of AAM:SBR:CMC = 100:0.7:1. Next, the negative electrode slurry is coated on both sides of the negative electrode current collector to form a coating film, and then the coating film is dried to form the AAM layer. Next, the negative electrode current collector with the AAM layer is calendered to a specified thickness using calendering rollers. The negative electrode in Example 1 is produced as described above.

[0095] [Making a Secondary Battery]

[0096] First, the positive and negative electrodes are cut to obtain a positive electrode sheet (CAM layer / positive current collector / CAM layer) and a negative electrode sheet (AAM layer / negative current collector / AAM layer). Additionally, a separator with a double-layer structure of polyethylene / heat-resistant layer is prepared. Next, they are stacked such that the heat-resistant layer of the separator is in contact with the CAM layer of the positive electrode sheet, with the positive current collector exposed, to obtain a stacked electrode body. Then, the positive current collector (aluminum foil) of the positive electrode sheet in this stacked electrode body is welded to an external positive current collector wire (aluminum plate), and the negative current collector (copper foil) of the negative electrode sheet is welded to an external negative current collector wire (copper plate). Next, the electrode body with the wire is inserted into an outer casing (a bag made of aluminum laminate film), a non-aqueous electrolyte is injected into the outer casing, and after standing for 12 hours, the outer casing is sealed. The non-aqueous electrolyte comprises a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (EC:EMC:DMC = 30:30:40 [volume ratio]) and LiPF6 dissolved therein as the electrolyte (concentration: 1.15 mol / L). Thus, the secondary battery (lithium-ion battery) for evaluation of Example 1 is obtained. In this secondary battery, the stacked electrode body and the non-aqueous electrolyte are contained within an outer casing (bag), with a portion of the front end of each of the positive and negative electrode wires of the stacked electrode body exposed outside the outer casing.

[0097] [Example 2]

[0098] Except for the following aspects, the secondary battery of Example 2 was prepared by the same method as that of Example 1. In the preparation of the second mixed powder for the second layer of the CAM layer, the above-mentioned W proportion in the second mixed powder was 2.0 mol%. The particles in the obtained second CAM powder were second CAM particles with a surface rich in tungsten (Li(Li)). 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.02 O2, W ratio: 2.0 mol%, average particle size D 50 (5.0μm).

[0099] [Example 3]

[0100] Except for the method for manufacturing the second positive electrode active material used in the second layer of the CAM layer, the secondary battery of Example 3 was manufactured by the same method as that of the secondary battery of Example 1. The method for manufacturing the second positive electrode active material in Example 3 was the same as that for manufacturing the first positive electrode active material in Example 1, except that ball milling was not performed.

[0101] In the CAM precursor preparation process, the stirring speed of the reaction solution during the crystallization reaction was set to 500 rpm. In the first calcination treatment, the calcination temperature was set to 800℃ and the calcination time was set to 15 hours. The W content in the mixed powder was set to 2.5 mol%. The particles in the obtained second CAM powder were tungsten-rich second CAM particles (Li(Li)). 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.025 O2, W concentration: 2.5 mol%, average particle size D 50 (12μm).

[0102] [Example 4]

[0103] In the fabrication of the first CAM used in the first layer, the preparation of the second mixed powder and the subsequent firing process were not carried out. Otherwise, the secondary battery of Example 4 was fabricated by the same method as the secondary battery of Example 1.

[0104] [Example 5]

[0105] In the formation of the CAM layer, the thickness ratio of the second layer in each CAM layer (70 μm) was set to 50%. Otherwise, the secondary cell of Example 5 was fabricated using the same method as the secondary cell of Example 1.

[0106] [Example 6]

[0107] Except for the following aspects, the secondary battery of Example 6 was prepared by the same method as that of Example 1. In the preparation of the first mixed powder for the first layer of the CAM layer, the W proportion in the first mixed powder was set to 0.7 mol%. The particles in the obtained first CAM powder were first CAM particles (Li(Li)) with a surface rich in tungsten. 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.007 O2, W concentration: 0.7 mol%, average particle size D 50 (10μm).

[0108] [Example 7]

[0109] In the formation of the CAM layer, the thickness of the second layer in each CAM layer (70 μm) was set to 60%. Otherwise, the secondary cell of Example 7 was fabricated by the same method as the secondary cell of Example 1.

[0110] [Example 8]

[0111] In the formation of the CAM layer, the second positive electrode slurry is not used. Instead, the first positive electrode slurry (containing the first CAM) forms a CAM layer with a thickness of 70 μm on both sides of the positive electrode current collector. Otherwise, the secondary battery of Example 8 is made by the same method as the secondary battery of Example 1.

[0112] [Example 9]

[0113] In the formation of the CAM layer, the first positive electrode slurry was not used. Instead, a CAM layer with a thickness of 70 μm was formed on both sides of the positive electrode current collector by the second positive electrode slurry (containing the second CAM). Otherwise, the secondary battery of Example 9 was prepared by the same method as the secondary battery of Example 1.

[0114] [Example 10]

[0115] In the fabrication of the second CAM used in the second layer, the preparation of the second mixed powder and its subsequent firing process were not carried out. Otherwise, the secondary battery of Example 10 was fabricated by the same method as the secondary battery of Example 1.

[0116] [Example 11]

[0117] Except for the following aspects, the secondary battery of Example 11 was prepared by the same method as that of Example 1. In the preparation of the second mixed powder for the second layer of the CAM layer, the W content in the second mixed powder was 0.5 mol%. The particles in the obtained second CAM powder were tungsten-rich second CAM particles (Li(Li)). 0.05 Ni 0.8 Co 0.1 Mn 0.1 W 0.005 O2, W concentration: 0.5 mol%, average particle size D 50 (4.0μm).

[0118] [Example 12]

[0119] The ball milling process described above was not performed on the second CAM layer used for the second CAM layer. Otherwise, the secondary cell of Example 12 was produced by the same method as the secondary cell of Example 1.

[0120] <Compositional Analysis of Positive Electrode Active Material>

[0121] The composition of each positive electrode active material (CAM) in Examples 1 to 12 was confirmed using an ICP emission spectrometer (product name "SPS3520UV-DD", manufactured by Hitachi High-Techscience).

[0122] <Particle size>

[0123] For the first CAM particles and the second CAM particles mentioned in Examples 1 to 12, the average particle size D was measured using a laser diffraction particle size distribution measuring device (product name "MT3000II", manufactured by Microtrac·BEL). 50 The results are shown in Table 1.

[0124] <Average Particle Intensity>

[0125] For the first CAM particle and the second CAM particle mentioned in Examples 1 to 12, the average particle intensity was investigated according to the following method.

[0126] The particle strength was determined using an Elionix ENT-5 micro-indentation hardness tester. Specifically, CAM particle powder was first fixed as a sample on the instrument's stage. Next, using the instrument's optical microscope, 10 random particles from the sample were selected, and the position coordinates of each particle on the stage were recorded. For each particle, the diameter (d) was measured from an image captured by the instrument's camera. Then, the stage was moved to be directly below a downward-facing flat indenter mounted on the instrument. Next, based on the position coordinates of a specified particle (target particle), the stage was finely adjusted so that the flat indenter was directly above the particle. Then, the flat indenter was lowered relative to the target particle on the stage, and the pressure required to crush the particle was measured. During this measurement, the amount of particle deformation was automatically measured while a test force (pressure) was gradually increased proportionally to the particle. This measurement determined the test force P (MPa) at the moment the particle crushed (deformed rapidly). Next, the crushing strength St (MPa) is calculated based on Equation (2) shown in JIS Z 8844 (2019) using the experimental force P and the particle diameter d (μm). Then, the average crushing strength St obtained for 10 particles is used as the average particle strength (MPa) for calculation. Its value is shown in Table 1.

[0127] St = 2.8P / πd 2 ···(2)

[0128] <Average roundness>

[0129] For the first CAM particles and the second CAM particles mentioned in Examples 1 to 12, the average roundness was investigated according to the following method.

[0130] First, the roundness of the CAM particles (powder) being measured was analyzed using a Morphologi4 particle image analysis device (manufactured by Malvern Panalytical). Specifically, the roundness (4πS / L) of 50 randomly selected particles from the powder was measured. 2(S is the area of ​​the particle, and L is the circumference of the particle image). Next, the average roundness of the 50 particles is calculated. This is defined as the average roundness. This value is shown in Table 1.

[0131] <Amount of covered elements>

[0132] For the CAM particles (CAM particle 1 and CAM particle 2) in Examples 1-12 containing tungsten (W), the presence of W as a surface element was confirmed by LA-ICP-MS analysis. In the CAM particles prepared as described above, the higher the proportion of W (coating element) relative to its constituent metal elements (Ni, Co, Mn), the higher the proportion of W (coating element) in the surface layer. For CAM particles containing W, the proportion of W relative to the total amount of its constituent metal elements (Ni + Co + Mn) is shown in Table 1 as the amount of coating element (mol%).

[0133] <Energy Density>

[0134] The energy density of each secondary battery in Examples 1 to 12 was investigated using the following method.

[0135] First, at 25°C, the secondary battery was subjected to a constant current density (0.2 mA / cm²). 2 The device is charged with a constant current until the voltage reaches 4.18V, and then charged with a constant voltage (4.18V) until the current density reaches 0.04mA / cm². 2 Next, at 25°C, the secondary battery was subjected to a constant current density (0.2 mA / cm²). 2 A constant current discharge was performed until the voltage reached 3.48V, and the discharge capacity (discharge energy) was measured. Then, the discharge capacity (Wh) was divided by the volume (L) of the secondary battery to calculate the energy density (Wh / L) of the secondary battery. The energy densities of each secondary battery are shown in Table 1 as relative values ​​when the energy density of the secondary battery in Example 8 is 100.

[0136] <Gas production during preservation experiment>

[0137] The following storage test was conducted on each of the secondary batteries in Examples 1 to 12 to investigate the amount of gas produced.

[0138] First, the volume (initial volume) of the secondary cell was determined using the Archimedes method. Fluorinert was used as the liquid in the Archimedes method. Next, the secondary cell was subjected to a constant current density (0.2 mA / cm²) at 25°C. 2 The device is charged with a constant current until the voltage reaches 4.2V, and then charged with a constant voltage (4.2V) until the current density reaches 0.04mA / cm². 2Next, the charged secondary battery was stored in a constant temperature bath at 60°C for 5 days. Then, the secondary battery was cooled at 25°C. Next, the volume of the cooled secondary battery (volume after storage) was measured using Archimedes' method under the same conditions as the initial volume measurement. Then, the difference (mL) between the volume after storage and the initial volume was calculated and used as the gas production amount. The gas production amounts of each secondary battery are shown in Table 1 as relative values ​​when the gas production amount of the secondary battery in Example 8 is 100.

[0139] [Table 1]

[0140]

[0141] As shown in Table 1, among the secondary batteries of Examples 1-12, the secondary battery of Example 8 produced the most gas. This can be attributed to the fact that the CAM layer (composed of a monolayer containing CAM particles with low average particle strength) of the secondary battery of Example 8 produced the most particle cracks during the CAM layer rolling process. Among the secondary batteries of Examples 1-12, the secondary battery of Example 9 had the lowest energy density. This can be attributed to the low CAM particle filling density in the CAM layer (composed of a monolayer containing CAM particles with high average particle strength) of the secondary battery of Example 9. The secondary battery of Example 10 produced a relatively large amount of gas, second only to Example 8. This can be attributed to the insufficient particle strength in the second layer (the second CAM particles do not contain coating elements), leading to an increase in particle cracks during the CAM layer rolling process and a decrease in tolerance to side reactions accompanying gas production. The secondary battery of Example 11 produced a relatively large amount of gas, second only to Examples 8 and 10. The reason for this can be attributed to insufficient coating element content of the second CAM particles in the second layer (where the coating element content of the second CAM particles is the same as that of the first CAM particles in the first layer), leading to insufficient particle strength and increased particle cracking during the CAM layer calendering process. Similar to the secondary battery in Example 11, the secondary battery in Example 12 exhibits a relatively high gas production, second only to Examples 8 and 10. The reason for this can be attributed to the low average sphericity of the second CAM particles in the second layer of the CAM layer in Example 12, resulting in insufficient particle slippage. Consequently, the effective load on the particles increases during the CAM layer calendering process, leading to increased particle cracking.

[0142] In contrast, the secondary batteries in Examples 1-7 achieve both high energy density and suppression of gas generation during high-temperature storage tests. This can be attributed to the combined effect of multiple factors: the average particle strength of the second CAM particles in the second layer is higher than that of the first CAM particles in the first layer, thus suppressing pressing cracks in the second CAM particles during the CAM layer calendering process; the high average roundness of the second CAM particles ensures the sliding properties between them during this process; the lower average particle strength of the first CAM particles in the first layer compared to the second CAM particles in the second layer results in greater flexibility, thus fulfilling the buffering function of the first layer during this process; and the first CAM particles are more easily deformed under pressing load than the second CAM particles, thus achieving high filling capacity.

[0143] As described above, the following are examples of the specific technical methods disclosed herein.

[0144] Item 1:

[0145] A secondary battery includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode has a current collector and a positive electrode active material layer on the current collector. The positive electrode active material layer includes a first layer and a second layer. The first layer is located between the current collector and the second layer. The first layer contains first positive electrode active material particles, and the second layer contains second positive electrode active material particles. The average particle strength of the second positive electrode active material particles is higher than that of the first positive electrode active material particles, and is 190 MPa or more. The average sphericity of the second positive electrode active material particles is 0.95 or more.

[0146] Item 2:

[0147] According to the secondary battery described in item 1, the average particle strength of the first positive electrode active material particles is 160 MPa or less.

[0148] Item 3:

[0149] According to item 1 or 2, the secondary battery wherein the second positive electrode active material particles have a surface portion rich in at least one element selected from group VIB and group IIIA elements.

[0150] Item 4:

[0151] The secondary battery according to any one of items 1 to 3, wherein the proportion of the elements selected from the group VIB and group IIIA elements to the total amount of Ni, Co and Mn in the second positive electrode active material particles is 0.8 mol% to 3.0 mol%.

[0152] Item 5:

[0153] The secondary battery according to any one of items 1 to 4, wherein the element selected above is tungsten.

[0154] Item 6:

[0155] The secondary battery according to any one of items 1 to 5, wherein the proportion of the elements selected from the group VIB and group IIIA elements relative to the total amount of Ni, Co and Mn in the first positive electrode active material particles is less than 0.8 mol.

[0156] Item 7:

[0157] The secondary battery according to any one of items 1 to 6, wherein the thickness of the second layer is in proportion to the total thickness of the positive electrode active material layer of 5% to 65%.

[0158] Item 8:

[0159] The secondary battery according to any one of items 1 to 7, wherein the average particle size D of the first positive electrode active material particles is... 50 The size ranges from 5μm to 18μm.

[0160] Item 9:

[0161] The secondary battery according to any one of items 1 to 8, wherein the average particle size D of the second positive electrode active material particles is... 50 The size ranges from 3μm to 15μm.

[0162] Item 10:

[0163] The secondary battery according to any one of claims 1 to 9, wherein the positive electrode active material constituting the first positive electrode active material particles and / or the second positive electrode active material particles is a positive electrode active material having the compositional formula Li(Li) a Ni x Co y Mn z M α O2 [where -0.1≤a≤0.1, 0.7≤x≤1, 0≤y≤0.3, 0≤z≤0.3, x+y+z=1, 0≤α≤0.1, and M is at least one element selected from B, Al, Mg, Ca, Ti, V, Cr, Ga, Zr, Nb, Mo, In, Hf, Ta, W, Tl] represents a lithium composite oxide.

[0164] The specific examples of the present invention have been described in detail above, but these are merely examples and do not limit the scope of protection claimed. The technology described in the scope of protection includes various modifications and variations of the specific examples illustrated above.

Claims

1. A secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode has a current collector and a layer of positive electrode active material on the current collector. The positive electrode active material layer comprises a first layer and a second layer, with the first layer located between the current collector and the second layer. The first layer contains first positive electrode active material particles. The second layer contains a second positive electrode active material particle. The average particle strength of the second positive electrode active material particles is higher than that of the first positive electrode active material particles, and is above 190 MPa. The average roundness of the second positive electrode active material particles is above 0.

95.

2. The secondary battery according to claim 1, wherein, The average particle strength of the first positive electrode active material particles is below 160 MPa.

3. The secondary battery according to claim 1, wherein, The second positive electrode active material particle has a surface layer rich in at least one element selected from group VIB and group IIIA elements.

4. The secondary battery according to claim 3, wherein, The proportion of the elements selected from Group VIB and Group IIIA elements in the second positive electrode active material particles relative to the total amount of Ni, Co and Mn is 0.8 mol% to 3.0 mol%.

5. The secondary battery according to claim 3, wherein, The selected element is tungsten.

6. The secondary battery according to claim 3, wherein, The proportion of the elements selected from Group VIB and Group IIIA elements in the first positive electrode active material particles relative to the total amount of Ni, Co and Mn is less than 0.8 mol.

7. The secondary battery according to claim 1, wherein, The thickness of the second layer is 5% to 65% of the total thickness of the positive electrode active material layer.

8. The secondary battery according to claim 1, wherein, The average particle size D of the first positive electrode active material particles 50 The size ranges from 5μm to 18μm.

9. The secondary battery according to claim 1, wherein, The average particle size D of the second positive electrode active material particles 50 The size ranges from 3μm to 15μm.

10. The secondary battery according to any one of claims 1 to 9, wherein, The positive electrode active material constituting the first positive electrode active material particle and / or the second positive electrode active material particle is a positive electrode active material having the compositional formula Li (Li a Ni x Co y Mn z M α The lithium composite oxide represented by O2 has the following composition: -0.1≤a≤0.1, 0.7≤x≤1, 0≤y≤0.3, 0≤z≤0.3, x+y+z=1, 0≤α≤0.1, and M is at least one element selected from B, Al, Mg, Ca, Ti, V, Cr, Ga, Zr, Nb, Mo, In, Hf, Ta, W, and Tl.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2023167298A